2021
DOI: 10.28940/terra.v39i0.829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del rendimiento, características morfológicas y químicas de variedades del maíz morado (Zea mays L.) en la región Cajamarca-Perú

Abstract: El Perú tiene una gran diversidad de productos agrícolas, debido a la variedad de climas y diversidad geográf ica, por lo que cuenta con siete principales razas del maíz morado. Por tanto, el objetivo del presente trabajo de investigación fue evaluar el rendimiento, las características morfológicas y químicas de cinco variedades del maíz morado, las cuales fueron el INIA-601, maíz morado mejorado MMM (variedad experimental), UNC-47, INIA-615 y PM-581 y la raza Canteño como control en dos niveles altitudinales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Despite their phenotypic diversity, studies based on morphological typing and archaeological evidence suggest that all purple maize landraces in Peru originated from the ancient race called ‘Kculli’ [ 5 ], or ‘Kulli sara’, which has been cultivated in Peru since prehispanic times [ 9 ]. Currently, there are six widely used landraces of purple maize (Morado de Cusco, Morado Canteño, Morado de Caraz, Morado Arequipeño, Negro de Junín, and Huancavelicano) and five improved cultivars (‘INIA-615 Negro Canaán’, ‘INIA-601’, ‘PM-581’, ‘PM-582’, and ‘UNC-47’) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their phenotypic diversity, studies based on morphological typing and archaeological evidence suggest that all purple maize landraces in Peru originated from the ancient race called ‘Kculli’ [ 5 ], or ‘Kulli sara’, which has been cultivated in Peru since prehispanic times [ 9 ]. Currently, there are six widely used landraces of purple maize (Morado de Cusco, Morado Canteño, Morado de Caraz, Morado Arequipeño, Negro de Junín, and Huancavelicano) and five improved cultivars (‘INIA-615 Negro Canaán’, ‘INIA-601’, ‘PM-581’, ‘PM-582’, and ‘UNC-47’) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent comparison between improved cultivars and landraces showed that cv. ‘INIA 601’ produces higher yields and higher concentration of anthocyanins than other improved purple maize landraces and cultivars [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, maize plants of the Kculli race, cultivated under an adequate scheme of chemical fertilization, irrigation and contribution of organic matter, can reach up to 4 m [ 20 ]. These are heights that, due to various biotic and abiotic factors to which the maize plants are exposed, they do not usually reach [ 36 , 63 , 64 ]. In addition, the fertilizer dose, the genotype used and the harvest year are other factors that influence the adequate use of N, P and K fertilizer by maize plants [ 65 ].…”
Section: Resultsmentioning
confidence: 99%